APU-PLUS: una solución complementaria para gamificar dinámicas escolares en el contexto virtual - Garay Bejar, Juan Roger (2020)
According to our own survey, carried out in Metropolitan Lima, more than 78% of regular basic education teachers who work in urban schools feel that they are not prepared to carry out virtual classes. This is because more than 72% of teachers have not received training in ICT. Likewise, of the digital tools provided by the Aprendo en Casa program, they only use the basic functionalities of video conference applications, such as zoom, Google meet and WhatsApp, for the development of their virtual classes. Additionally, teachers feel that the digital gamification tools currently provided are limited and complicated to use. In this sense, in this project, an APU-PLUS is proposed as an alternative to reinforce the learning process and allow, to design school gamified dynamics in a simple and intuitive way. To identify the teacher's need, Design Thinking and UX (user experience) were used. On the other hand, for the construction of the APU-PLUS application, agile methodologies (simple design, refactoring and unit tests) and the Scrum framework for the management of the software project were used. Regarding the results, the APU-PLUS MVP was tested and qualified by the teachers through usability tests. Teachers find the APU-PLUS app easy to use and useful for creating gamified dynamics.